First-principles study on electronic and optical properties of Zn-substituted CuGaSe2 - Yiming Ren; Yonghong Hu; Zhenglong Hu; Li Xue (Results in Physics, 2021)
The effects of Zn atoms on the electronic and optical properties of CuGaSe2 have been investigated by the first-principles calculations. In this work, we discuss three possible substitution ways for Cu and Ga atoms of CuGaSe2 substituted by Zn atoms. First, we estimate the formation energies of Zn-substituted CuGaSe2. And then the energy band structures, densities of state and optical properties are calculated with MBJ-LDA. The spectra of reflectivity and absorption coefficients show that the participation of Zn can reduce the reflectivity of CuGaSe2 in the range 1–5 eV, and improve the absorption coefficients of solar cells in the low energy range.